The problem of formation of artistic and professional skills in the process of training educational teachers in the arts in higher educational institutions - A.A. Marchenko (Academy of Cognitive and Natural Sciences, 2009)
Thu article is devoted a question of training future visual arts teachers. Here are (unsized features of formation art abilities in the process of professional students training in visual- pedagogical specialities.